EVALUATION OF LOCAL RECURRENCE OF BREAST CONSERVATION SURGERY AT THE CEARÁ INSTITUTE OF CANCER - Magalhães, Giovanni de Freitas; Cavalcante, Francisco Pimentel; Lima, Marcos Venício Alves; Castro, Rafael Bustamante de (Mastology, 2019)
Introduction: Breast cancer is the most common malignant tumor in the world, with the exception of cases of non-melanoma skin cancer. In Brazil, more than 56,000 cases were estimated for 2016. The expected mortality rate remains high because of late diagnosis. Nowadays, conservative surgery is the gold standard treatment. Objective: To evaluate the locoregional recurrence of conservative surgery practiced at the Ceará Institute of Cancer, between 2002 and 2012. Method: A cross – sectional study with a descriptive approach using secondary data obtained from the medical records of patients with breast cancer operated at the Ceará Institute of Cancer. Results: The study population consisted of 360 patients. Invasive ductal carcinoma was the most common type (72.8%), followed by ductal carcinoma in situ (16.4%) and invasive lobular carcinoma (4.7%). The other histological types represent 6.4% (cribriform, 0.5%, medullary, 0.6%, micro invasive, 0.3%, mucinous, 1.1%, papillary, 3.1% 8%; and tubular, 0.8%). In the sample, 25 patients had some type of recurrence: 13/360 (3.6%), local or locoregional; and 12/360 (3.3%), distant recurrence. Conclusion: From the data analysis, we can conclude that the conservative surgery practiced at the Ceará Institute of Cancer showed data on recurrence compatible with the international literature.